2022
DOI: 10.3390/ijms232113137
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of A Magnetic Nanoparticle-Modified Root Canal Sealer on Persistent Apical Periodontitis

Abstract: Persistent apical periodontitis is a critical challenge for endodontists. Developing root canal filling materials with continuous antibacterial effects and tightly sealed root canals are essential strategies to avoid the failure of root canal therapy and prevent persistent apical periodontitis. We modified the EndoREZ root canal sealer with the antibacterial material dimethylaminododecyl methacrylate (DMADDM) and magnetic nanoparticles (MNPs). The mechanical properties of the modified root canal sealer were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Multispecies biofilm, a common form of root-canal bacteria, provided a more realistic representation of the complexity of root-canal infections [ 46 , 47 ]. Thus, it was used in our study as a crucial method of assessing the antimicrobial efficacy of intracanal medicaments.…”
Section: Discussionmentioning
confidence: 99%
“…Multispecies biofilm, a common form of root-canal bacteria, provided a more realistic representation of the complexity of root-canal infections [ 46 , 47 ]. Thus, it was used in our study as a crucial method of assessing the antimicrobial efficacy of intracanal medicaments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with an external magnetic field, the modified sealer might broaden its area of penetration and have a considerable antibacterial impact on multispecies biofilms. The in vivo investigation found that the sealer with 2.5% DMADDM and 1% MNP had a good inhibitory effect on persistent apical periodontitis because it prevented considerable resorption and only slightly increased the PDL space at the apices of root canals [ 119 ]. Another research will examine how IONPs impact rat collagenase-1 (COL-1) and ALP levels as well as periodontal disease.…”
Section: Metal Nanoparticles In Periodontitismentioning
confidence: 99%